Thiolated-Polymer-Based Nanoparticles as an Avant-Garde Approach for Anticancer Therapies—Reviewing Thiomers from Chitosan and Hyaluronic Acid - Roberto Grosso; M.-Violante de-Paz (Pharmaceutics, 2021)
Thiomers (or thiolated polymers) have broken through as avant-garde approaches in anticancer therapy. Their distinguished reactivity and properties, closely linked to their final applications, justify the extensive research conducted on their preparation and use as smart drug-delivery systems (DDSs). Multiple studies have demonstrated that thiomer-rich nanoformulations can overcome major drawbacks found when administering diverse active pharmaceutical ingredients (APIs), especially in cancer therapy. This work focuses on providing a complete and concise review of the synthetic tools available to thiolate cationic and anionic polymers, in particular chitosan (CTS) and hyaluronic acid (HA), respectively, drawing attention to the most successful procedures. Their chemical reactivity and most relevant properties regarding their use in anticancer formulations are also discussed. In addition, a variety of NP formation procedures are outlined, as well as their use in cancer therapy, particularly for taxanes and siRNA. It is expected that the current work could clarify the main synthetic strategies available, with their scope and drawbacks, as well as provide some insight into thiomer chemistry. Therefore, this review can inspire new research strategies in the development of efficient formulations for the treatment of cancer.